The Importance of Mapping Determinants, Attitudes and Beliefs of Vaccine Hesitancy in the Great Challenge of Compulsory Childhood Vaccination; Comment on "Convergence on Coercion: Functional and Political Pressures as Drivers of Global Childhood Vaccine Mandates" - Federica Guaraldi; Marco Montalti; Davide Gori (Kerman University of Medical Sciences, 2023)
Vaccine hesitancy (VH) has risen significantly during the COVID-19 pandemic, becoming a major global health concern. VH is characterized by the delay or refusal of vaccination despite its availability. Various frameworks have been developed to understand the complex factors influencing VH, with attitudes, beliefs, and external influences being the most significant. The surge in VH has reignited the debate on the best approach to address it: persuasive/educational or coercive. Attwell and Hannah studied the political and social reasons behind the adoption of mandatory vaccination in four jurisdictions (Italy, France, Australia, and California) due to declining vaccine coverage below the safety threshold. However, these methods may foster parental disbeliefs and opposition to vaccination campaigns. To combat VH, it is crucial to systematically assess its determinants within specific contexts and population groups. Increasing awareness about vaccination benefits, engaging with social media, and employing tailored strategies can foster spontaneous adherence to vaccination programs, eliminating the need for coercive measures.